Adverse effects during treatment with renin–angiotensin–aldosterone system inhibitors; should we stay or should we stop?. Issue 3 (15th May 2023) - Leon, Silvia J.; Carrero, Juan Jesus
Abstract : Purpose of review: To discuss recent evidence on the benefits and harms of stopping therapy with renin–angiotensin–aldosterone system inhibitors (RAASi) after the occurrence of adverse events or in patients with advanced chronic kidney disease (CKD). Recent findings: RAASi may result hyperkalemia or acute kidney injury (AKI), particularly in persons with CKD. Guidelines recommend to temporarily stop RAASi until the problem is resolved. However permanent discontinuation of RAASi is common in clinical practice with the potential to heighten subsequent cardiovascular disease (CVD) risk. A series of studies evaluating the consequences of stopping RAASi (vs. continuing) after an episode of hyperkalemia or AKI consistently report worse clinical outcomes, both higher risk of death and cardiovascular events. The STOP-angiotensin converting enzyme inhibitors (ACEi) trial and two large observational studies also favor the decision to continue ACEi/ angiotensin receptor blockers in advanced CKD, refuting old observations that use of these medications can accelerate the risk of kidney replacement therapy. Summary: Available evidence suggests continuing with RAASi after the occurrence of adverse events or in patients with advanced CKD, primarily attributed to sustained cardioprotection. This is in line with current guideline recommendations.